Nomenclatural note for Pedicularis oederi var. angustiflora (Orobanchaceae) - Yu, Wen-Bin; Wang, Hong; Li, De-Zhu (Phytotaxa, 2014)
The genus Pedicularis L. comprises approximately 600 species (Li 1948; Fischer 2004), and as such, it is the largest genus of the family Orobanchaceae (Olmstead 2012). More than 350 species are recorded from China (Yang et al. 1998). In this study, the validity of Tsoong’s (1963: 334) new combination P. oederi var. angustiflora (H.Limpricht) P.C.Tsoong and its taxonomical history are discussed, and a lectotype is designated.